Community Participation in The Successful Community Empowerment Program (Prodamas) In Ngronggo Village Kediri City - Tamrin, M. Husni; Fatimah, Salma Syenita Nur; Wahyuni, Sri (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe and analyze the implementation of the Community Empowerment Program (Prodamas), forms of community participation and also the role of the government in increasing community participation in Ngronggo Village. This research is a qualitative research with a case study approach and uses data collection techniques through interviews with several informants who are considered to be able to provide clear information regarding the effectiveness of Prodamas in Ngronggo Village, Kediri City. In addition to interviews, data collection techniques are also in the form of observation, documentation and triangulation. The results of this study indicate that Prodamas has been running in accordance with the regulations of the City of Kediri and community participation is a very influential factor in the success of the Community Empowerment Program